Identity and community in the gay world - Warren, Carol A. B. (New York : Wiley, 1974)
An ethnographic and theoretical study of identity, community, world, and gayness. The widest focus of the book is world, and the narrowest is identity.
Part 1. Community -- Part 2. Society -- Part 3. Identity.
Includes bibliographical references.
Keywords: HOMOSEXUALITY, UNITED STATES